Improvised dynamic network connectivity model for Vehicular Ad-Hoc Networks (VANETs). (15th November 2018) - Das, Debasis; Misra, Rajiv
Abstract: The Road traffic modeling in Vehicular Ad Hoc Networks (VANETs) may require disseminating information to specific geographical areas like Road Intersection. The communications, network connectivity and routing are the central issues in VANETs. The Vehicular Ad Hoc Network (VANETs) have high mobility and high density of mobile nodes. Managing this mobility is very important to ensure routing efficiency and network connectivity in VANETs. VANETs are characterized by topology changes and link disconnections. The research challenges for applications of VANETs remains to design of intelligent algorithms for dynamic network connectivity and efficient routing problem in VANETs becomes a challenging event because of the active nature of mobile clients. In this paper, we have proposed an appropriate routing protocol for VANETs based on the dynamic network connectivity behavior of urban traffic at road crossings or Intersection. The dynamic network connectivity model for VANETs is based on parallel processing concept are essential for designing an efficient routing protocol for VANETs at Road Intersection in urban scenarios. Our simulation result showed that different control mechanisms are applied at road crossings and we likened the performance of our proposed scheme with the competitive schemes (Modeling Urban Traffic (MUT) Scheme, Dynamic Connectivity Scheme (DCS), Cellular Automaton Model for Car Traffic (CAMCT) and Dynamic Connectivity-Aware Routing for Internet-based Services (D-CAR)) in terms of Inter-vehicle spacing, number of vehicles in one road block and distance from road crossings or Intersection against varying node density.